Study on Correlation between Brandwein Points Based Histological Grading and Clinical Features of Mucoepidermoid Carcinoma of Salivary Glands (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Mucoepidermoid Carcinoma (MEC) is the one malignancy in which histologic grading correlate with clinical behavior. The findings of the current study revealed that meticulous, uniform histopathologic grading is of importance of MEC of salivary glands. The aim of our study is to evaluate correlation between histopatholological grading with clinical features of mucoepidermoid carcinoma of salivary glands.Materials and methods: This cross sectional study was conducted in patient attending tertiary level hospital in Dhaka, Bangladesh. A total 20 patients of histopathological grading of the mucoepidermoid carcinoma of salivary glands were undertaken using the currently established Brandwein point based histological grading systemand also evaluated the clinical features of the patients according to age sex and location. The data obtained were recorded and statistically analyzed.Results: Twenty patients with mucoepidermoid carcinoma of salivary glands clinically and histopathologically evaluated. All tumors were graded histopathologically based on the criteria Brandweinpoint based histological grading system that among the 20 respondents 8 (40.0%) were diagnosed as MEC low grade, intermediate MEC 8 (40.0%), 4 (20.0%) were found as MEC high grade. Low grade tumors were not present any defining histolgical feature, intermedtate grade tumors revealed no bony invasion and necrosis but high grade tumors got all defining features.Conclusion: Histological grading of MEC mucoepidermoid carcinoma of salivary glands which is apparently correlate with clinical findings found in our study.JCMCTA 2022 ; 33 (2) : 66-71